The Oxford English dictionary / on compact disc. - Oxford University Press (New York : Oxford University Press, 1992)
A complete text of the 2nd ed. of the Oxford English dictionary with search software which allows the user to locate a specific word; browse the text; formulate complex searches using Boolean operators; limit searches by date, part of speech, or section of the entry; follow up cross-references; save search results to a file; or paste sections of the OED2 into a text file.
Title from disk label.
Ed. statement from label mounted on container: PC version.
System requirements: IBM-compatible PC with 386 processor; 2MB RAM (4MB recommended); DOS 3.0 or higher; Windows 3.0 or higher; Microsoft CD-ROM Extension software (MSCDEX 2.0 or higher); hard disk with 1MB free space; VGA monitor; CD-ROM drive; mouse.
Keywords: English language -- Dictionaries -- Databases